Analysis of Factors Affecting Islamic Insurance Profitability (Case Study Of Sinar Mas Islamic Insurance Period 2011-2017) - Nurbaya, Siti; Alam, Azhar (Journal of Islamic Economic Laws, 2019)
Profitability is one benchmark to show a company operational performance. Various factors influence the amount of profitability. This research aims to analyze the influence of the amount of premium income, total investment, claims expense and operational costs on the profitability gained during the period 2011-2017. This paper conducts multiple linear analysis, namely OLS (Ordinary Least Square) with secondary data in the form of time-series data. The results of the t-test indicate that the claims expense variable has a negative and significant effect. Meanwhile, the operational cost variable has a positive and significant impact. On the contrary, the premium variable and the amount of investment both have a positive but not significant effect. Moreover, the results of the F test show that the variables of premium, investment, claims expense and operating costs have a considerable impact on the profitability of Sinar Mas Islamic Insurance.